Put a ring on it: application of small aliphatic rings in medicinal chemistry - Bauer, Matthias R; Di Fruscia, Paolo; Lucas, Simon C. C; Michaelides, Iacovos N; Nelson, Jennifer E; Storer, R. Ian; Whitehurst, Benjamin C (RSC medicinal chemistry, 2021)
Aliphatic three- and four-membered rings including cyclopropanes, cyclobutanes, oxetanes, azetidines and bicyclo[1.1.1]pentanes have been increasingly exploited in medicinal chemistry for their beneficial physicochemical properties and applications as functional group bioisosteres. This review provides a historical perspective and comparative up to date overview of commonly applied small rings, exemplifying key principles with recent literature examples. In addition to describing the merits and advantages of each ring system, potential hazards and liabilities are also illustrated and explained, including any significant chemical or metabolic stability and toxicity risks. Aliphatic small rings including cyclopropanes, cyclobutanes, oxetanes, azetidines and bicyclo[1.1.1]pentanes have been increasingly exploited in medicinal chemistry. This review summarises judicious successful application and reported limitations of these ring systems.